MAKNA GERAK TARI JEPIN MELAYU SAYAN DI DUSUN MUARA COMAT KECAMATAN SAYAN JAYA KABUPATEN MELAWI KALIMANTAN BARAT - Sawitri, Sari; Fratisari, Imma; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is motivated by the researcher?s desire to know the meaning of movement in Jepin Melayu Sayan dance in Melawi District, West Kalimantan. The purpose of this research is to describe Jepin Melayu Sayan dance along with the images in order to be clearly understood about the meaning contained in it. The research method used is descriptive method with qualitative research form by using ethnochoreology approach. The result of this research is a form of analysis about dance movement and meaning of Jepin Melayu Sayan dance movement. The dance and the meaning of dance movement that is studied and analyzed is the opening movement that is the respect to others, Balek Balang movement is the form of doubtful sense, Putar Angin movement is the expression of gratitude to natural phenomena, Tiung (parrots) dance movement is a form of admiration for a variety of natural wealth, and the closing movement is a sign of the end of Jepin Melayu Sayan. The result of the research on Jepin Melayu Sayan dance is expected to be used as a teaching material in the learning of art and culture for Grade VII SMP (Junior High School). Keywords: Meaning of Dance Movement, Jepin Melayu Sayan.